Biomechanics and Microstructural Analysis of the Mouse Knee and Ligaments - Carballo, Camila B.; Hutchinson, Ian D.; Album, Zoe M.; Mosca, Michael J.; Hall, Arielle; Rodeo, Scott, Jr.; Ying, Liang; Deng, Xiang-Hua; Rodeo, Scott A. (The Journal of Knee Surgery, 2018)
The purpose of this study is to determine the feasibility of using murine models for translational study of knee ligament injury, repair, and reconstruction. To achieve this aim, we provide objective, quantitative data detailing the gross anatomy, biomechanical characteristics, and microscopic structure of knee ligaments of 44 male mice (C57BL6, 12 weeks of age). Biomechanical testing determined the load-to-failure force, stiffness, and the site of ligament failure for the anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), and the medial and lateral collateral ligaments (MCL and LCL). These data are complemented by histological characterization of each of the knee ligaments. In addition, the osseous morphology of the mouse knee was examined using high-resolution nanofocus computed tomography (CT), while standard micro-CT was employed to measure bone morphometrics of the distal femur and proximal tibia. Collectively, our findings suggest that the gross anatomy of the mouse knee is similar to the human knee despite some minor differences and features unique to the murine knee. The ACL had the highest load to failure (5.60 ± 0.75 N), the MCL (3.33 ± 1.45 N), and the PCL (3.45 ± 0.84 N) were similar, and the LCL (1.44 ± 0.37 N) had the lowest load to failure and stiffness. Murine models provide a unique opportunity to focus on biological processes that impact ligament pathology and healing due to the availability of transgenic strains. Our data support their use as a translational platform for the in vivo study of ligament injury, repair, and reconstruction.
Keywords: biomechanics; micro-CT; knee ligaments; mouse; murine models